Incidence of Crohn's Disease and Ulcerative Colitis in Rhode Island: Report from the Ocean State Crohn's and Colitis Area Registry. Issue 6 (June 2016) - Shapiro, Jason M.; Zoega, Helga; Shah, Samir A.; Bright, Renee M.; Mallette, Meaghan; Moniz, Heather; Grabert, Stacey A.; Bancroft, Barbara; Merrick, Marjorie; Flowers, Nicole T.; Samad, Zahid; Lidofsky, Sheldon; et al.
Abstract : Background: Studies describing the incidence of Crohn's disease (CD) and ulcerative colitis (UC) are uncommon in the United States. We sought to determine the incidence of CD and UC in the state of Rhode Island. Methods: The Ocean State Crohn's and Colitis Area Registry is a state-based inception cohort of patients newly diagnosed with inflammatory bowel disease (IBD) in Rhode Island. To confirm a diagnosis of CD, UC, or IBD unclassified (IBDU), the National Institute of Diabetes and Digestive and Kidney Diseases IBD Genetics Consortium criteria were applied in a review of medical records from gastroenterology practices located in the state of Rhode Island and adjacent to the Rhode Island border in Massachusetts and Connecticut. Using population-based data, we determined the statewide incidence of IBD in Rhode Island from 2008 to 2010. Results: A total of 971 Rhode Island residents were diagnosed with IBD, including 444 with CD, 486 with UC, and 41 with IBD unclassified from 2008 to 2010. The overall age- and sex-adjusted IBD incidence was 30.2 (95% confidence interval, 28.3–32.1) per 100, 000 persons in this time frame with 13.9, 15.1, and 1.3 per 100, 000 diagnosed with CD, UC, and IBD unclassified, respectively. Of the total incident cases in Rhode Island, 30% (n = 291) were enrolled in Ocean State Crohn's and Colitis Area Registry for follow-up. Conclusions: The incidence of IBD in Rhode Island is higher than that previously reported by other population-based cohorts in the United States. Prospective follow-up of individuals enrolled in the community-based Ocean State Crohn's and Colitis Area Registry cohort is ongoing. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 1 March 2016.